2012
DOI: 10.1128/jvi.05741-11
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the RNA Silencing Suppression Activity of the Ebola Virus VP35 Protein in Plants and Mammalian Cells

Abstract: Ebola virus (EBOV) causes a lethal hemorrhagic fever for which there is no approved effective treatment or prevention strategy. EBOV VP35 is a virulence factor that blocks innate antiviral host responses, including the induction of and response to alpha/ beta interferon. VP35 is also an RNA silencing suppressor (RSS). By inhibiting microRNA-directed silencing, mammalian virus RSSs have the capacity to alter the cellular environment to benefit replication. A reporter gene containing specific microRNA target seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 57 publications
0
26
0
Order By: Relevance
“…Previous reports have shown that transient overexpression of the P19, NS3, VP35 and E3L proteins can suppress induced RNAi directed against reporter gene constructs in mammalian cells (Dunoyer et al, 2004;Haasnoot et al, 2007;Liu et al, 2012;Schnettler et al, 2008;Zhu et al, 2012). In addition, VP35, E3L and NS3 can complement the RNAi suppressor function of the HIV-1 Tat protein to support HIV-1 replication (Haasnoot et al, 2007;Schnettler et al, 2009).…”
Section: Discussionmentioning
confidence: 93%
“…Previous reports have shown that transient overexpression of the P19, NS3, VP35 and E3L proteins can suppress induced RNAi directed against reporter gene constructs in mammalian cells (Dunoyer et al, 2004;Haasnoot et al, 2007;Liu et al, 2012;Schnettler et al, 2008;Zhu et al, 2012). In addition, VP35, E3L and NS3 can complement the RNAi suppressor function of the HIV-1 Tat protein to support HIV-1 replication (Haasnoot et al, 2007;Schnettler et al, 2009).…”
Section: Discussionmentioning
confidence: 93%
“…While subsequent studies found that the C-terminal domain of VP35 bound to siRNA and not to dsRNA, the RNAi silencing suppression activity of VP35 did not correlate with binding to siRNA. It was hypothesized that suppression via RNA binding-independent mechanisms could instead occur through binding to the RISC complex or sequestration of RISC complex proteins prior to their incorporation into the complex (Zhu et al, 2012). This theory is supported by prior experiments that found VP35 interacts with transactivation response RNA-binding protein (TRBP) and PACT (Fabozzi et al, 2011), both components of the RISC RNAi complex and thus proposed to mediate the VP35-dependent RNA silencing suppressor activity.…”
Section: Silence Will Fall: Disrupting the Rnai Responsementioning
confidence: 99%
“…The VP35 proteins are innate immune antagonists that target RIG-I-like receptors (RLRs), PKR, and RNA silencing activity (Bale et al, 2012; Basler et al, 2003; Basler et al, 2000; Cardenas et al, 2006; Fabozzi et al, 2011; Feng et al, 2007; Haasnoot et al, 2007; Ramanan et al, 2012; Schümann et al, 2009; Zhu et al, 2012). RLRs detect viral nucleic acids and signal to induce an interferon (IFN)-α/β response (Leung et al, 2012).…”
Section: Introductionmentioning
confidence: 99%